Pengaruh Lingkungan Kerja, Disiplin Kerja, Dan Kompensasi Terhadap Kepuasan Kerja Pegawai Pada Kementerian Sosial Sentra Terpadu Pangudi Luhur Kota Bekasi - Khairani, Nila; Zahara Tussoleha Rony; Rycha Kuwara Sari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of the work environment, work discipline, and compensation on employees job satisfaction at kementerian social sentra terpadu pangudi luhur Bekasi City. The type of research used in this research is quantitative research. The sampling technique uses a non-probability sampling method with a saturated sampling technique (census), namely all members of the population sampled are 80 employees kementerian social sentra terpadu pangudi luhur Bekasi City. The data analysis method uses multiple linear regression and data were processed using IBM SPSS Statistics 26. The results of this study show that (1) The work environment has a significant effect on employees job satisfaction at kementerian social sentra terpadu pangudi luhur Bekasi City, (2) Work discipline has no a significant effect on employees job satisfaction at kementerian social sentra terpadu pangudi luhur Bekasi City, (3) Compensation has a significant effect on employees job satisfaction at kementerian social sentra terpadu pangudi luhur Bekasi City, and (4) The work environment, work discipline, and compensation simultaneously influence on employees job satisfaction at kementerian social sentra terpadu pangudi luhur Bekasi City.